RECENT EPIDEMIOLOGICAL AND CLINICAL INSIGHTS INTO EPSTEIN–BARR VIRUS INFECTION IN CHILDREN - Karshieva Barno Shamsiyevna; Rakhmonov Ravshan Nomozovich (Web of Journals Publishing, 2025)
This article summarizes the characteristics of the clinical course of infectious mononucleosis observed in 142 children aged 1 to 14 years residing in the Samarkand region. The findings indicate that, at the present stage, the disease continues to demonstrate its typical clinical manifestations. Timely and precise diagnosis of infectious mononucleosis significantly enhances treatment outcomes, as reflected by a shorter duration of fever, reduced intensity of lymph node proliferative syndrome, and more rapid resolution of cytolysis.
Keywords: Atypical mononuclear cells, children, Epstein–Barr virus (EBV), infectious mononucleosis.